This side of the grave : a Night Huntress novel - Frost, Jeaniene (Frost, Jeaniene. Night Huntress novel, 2011)
When vampires begin to disappear and rumors of a new war surface, Cat Crawfield and her vampire husband Bones are forced to align themselves with the ghoul queen of New Orleans.